FAKTOR – FAKTOR YANG MEMENGARUHI FINANCIAL PERFORMANCE PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Sofian, Stephanie Chrystella; Susanto, Liana (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to obtain empirical evidence regarding the effect of independent variables which are human capital efficiency, structural capital efficiency, capital employed efficiency, firm size, and capital structure on the dependent variable, financial performance in manufacturing companies in Indonesia. The sample on this study is limited on manufacturing companies listed on the Indonesia Stock Exchange during the year 2017-2020. This study uses purposive sampling method to collect data and EViews 12 for data processing. The results of this study conclude that human capital efficiency and capital employed efficiency have a positive influence on financial performance, while structural capital efficiency, firm size, and capital structure efficiency have no effect on financial performance.